Securitization of Immigration and Refugee Policy in Contemporary Islamic Politics and International Law - Firas Meshhal Abduljabbar; Saad Abdulhameed Shalev; Rami Salih; Oudha Yousif Salman Al-Musawi; Yurii Khlaponin (Faculty of Sharia, IAIN Metro, 2025)
The increasing number of migrants has strengthened the configuration of international relations and legal frameworks in contemporary Islamic politics. However, the concept of an Islamic political system remains ambiguous—whether it refers to countries that implement Islamic law, policies of Muslim-majority states, or the broader discourse on Islamic politics. This study explores the securitization of immigration and refugee policies in Muslim-majority countries by highlighting the connection between international refugee law and contemporary Islamic political principles. The analysis is conducted within a broader framework, examining the development of international refugee law and contemporary Islamic political responses to migration and refugee crises, particularly in Syria, Afghanistan, and Myanmar. Through doctrinal legal analysis and empirical case studies from Saudi Arabia, Turkey, and the United Arab Emirates, this research finds that many Muslim-majority countries have tightened border controls, restricting migrant and refugee access without adequate asylum mechanisms. Additionally, there has been an increase in asylum externalization policies, where responsibility for refugee protection is transferred to third countries, reducing the accountability of primary host nations. Detention policies are also becoming more common, with a growing number of detention centres and deportation practices that often violate contemporary Islamic political principles and international human rights commitments. Furthermore, findings indicate that in many cases, these securitization policies contradict Islamic values of protection and solidarity, which emphasize the rights of refugees and fair treatment for those seeking asylum. This study significantly contributes to evaluating the legal gaps between national policies, contemporary Islamic political principles, and international refugee law while offering policy recommendations that balance security concerns with human rights protection.